Implementing an Append-Only Interface for Semiconductor Storage - Reid, Colin; Bernstein, Phil (IEEE Data Eng. Bull., 2010)
Solid-state disks are currently based on NAND ﬂash and exposea standard disk interface. To accommodate limitations of the medium, solid-state disk implementations avoid rewriting data in place, instead exposing a logical remapping of the physical storage. We present an alternative way to use ﬂash storage, where an append interface is exposed directly to software. We motivate how an append interface could be used by a database system. We describe bit rot and space reclamation in direct-attached log structured storage and give details of how to implement the interface in a custom controller. We then show how to make append operations idempotent, including how to create a fuzzy pointer to a page that has not yet been appended (and therefore whose address is not yet known), how to detect holes in the append sequence, and how to scale out read operations.